Prognostic value of CT characteristics in GEP-NET: A systematic review. (July 2022) - van der Velden, D.L.; Staal, F.C.R.; Aalbersberg, E.A.; Castagnoli, F.; Wilthagen, E.; Beets-Tan, R.G.H.
Abstract: Aim: A range of CT characteristics with potential prognostic value have previously been identified for gastro-entero-pancreatic neuroendocrine tumors (GEP-NETs). Still, there is no widely accepted consensus on which characteristics should be reported as prognostic factors. This systematic review therefore aims to provide an overview of the available literature regarding CT characteristics and their prognostic significance for GEP-NET patients. Materials and methods: PubMed, Embase, and Scopus/Cochrane Library databases were searched and a forward and backward reference check of the identified studies was executed. Eligible studies were conducted in patients with GEP-NET, and reported on the prognostic significance (in terms of tumor grade, spread of disease, and survival) of CT-based biomarkers. Study selection, quality assessment and data extraction were performed by two reviewers independently, resolving disagreement by consensus. Results: In total, 5074 unique studies were identified, of which 37 were included. Given the paucity of data on GEP-NETs other than PNET, data extraction and analyses was restricted to PNETs. Fourteen CT characteristics were correlated to prognostic outcomes. Larger tumor size, hypo-enhancement, irregular shape and ill-defined margins, presence of locally invasive growth, lymphadenopathy and metastases were predictors of poorer prognosis according to 65–89% of the available studies. Most studies were regarded as having a low (65%) or moderate (24%) risk of bias. Conclusion: Evidence regarding prognostic value of CT-based biomarkers for PNETs is limited to heterogeneous, retrospective studies. Nonetheless, heterogeneity in data is more likely to obscure than to overestimate any correlation. Therefore, we feel that the before-mentioned characteristics should be regarded and reported as clinically relevant predictors of poorer prognosis. Graphical Abstract: ga1 Highlights: Evidence on the prognostic value of CT-based biomarkers for GEP-NETs is scarce. GE-NETs were left out of the analyses due to insufficient data. For PNETs, 37 studies were included. Studies were heterogeneous and retrospective. Overall, tumor size, enhancement, shape and spread have the most prognostic value.